The Urgency Of English In The Curriculum In Indonesia To Prepare Human Resources For Global Competitiveness - Dzulkifli Isadaud; M.Dzikrul Fikri; Muhammad Imam Bukhari (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
English is an international language and often this language is used as a second language in several countries. Coupled with the current developments, everyone must be able to master English fluently in order to be able to compete with the outside world or compete globally so that English is seen as a unifying tool nation and has an important role in life, especially in education. On the other hand, teaching English in Indonesia has been practiced since the Dutch colonial era until now. The purpose of writing this article is to explain the urgency of English. in the curriculum in Indonesia in order to prepare human resources that are globally competitive. The results of the information found that the use of English in the curriculum in Indonesia is still not implemented at all levels of education,learning English is only limited to students understanding "reading, listening, and writing, and speaking". However, students still have difficulty speaking using English because not as a second national language and what we need to know is the challenge of globalization which demands that our society understands English. Students still have difficulty speaking in English because it is not a national second language and what we need to know is the challenges of globalization that demand that our society understands English.Students still have difficulty speaking in English because it is not a national second language and what we need to know is the challenges of globalization that demand that our society understands English.